Where are the Mothers Going to Deliver? A Study of Birthplace Preference in a Rural Community in South-South Nigeria - Glory Ovunda Worgu; Prince Nukoamene Abueh; Siene Oluwatosin Orogun; Lisa Aleruchi Orianwo; Ekene Ajah (Nigerian Journal of Medicine)
Objectives: Despite significant investment in health facilities, 61% of births in Nigeria occur outside formal settings. This study aimed to determine birthplace preferences and their influencing factors amongst women of childbearing age in a rural community in South-South Nigeria. Methodology: A descriptive cross-sectional study was conducted with 606 women of childbearing age in a rural Rivers State community. Data were collected through a semi-structured e-questionnaire and analysed using SPSS version 25, employing descriptive and analytical statistics with a significance set at P ≤ 0.05. Results were displayed in charts and tables. Results: A significant number of mothers in the study were unable to read (68.8%), most were married (61.8%) and lived in nuclear families (57.3%), with an average age of 29.6 years (standard deviation = 7.4 years). The majority (87.1%) had at least one child, and about 19.8% had experienced child loss. In their last pregnancies, 89.2% delivered in non-formal settings, and 60.1% of those planning future deliveries intend to do the same. Factors such as illiteracy, lack of insurance, unemployment and having more than three children were linked to higher odds of delivering in non-formal places (adjusted odds ratio [aOR] [95% confidence interval (CI)]: 6.338 [1.856–21.641]; 9.023 [1.708–47.672]; 4.127 [2.131–7.991] and 4.645 [1.315–16.408], respectively). Illiteracy and higher parity were also associated with future delivery intentions in non-formal settings (aOR [95% CI]: 1.805 [1.148–2.84] and 3.943 [2.077–7.489], respectively). Half of the mothers suggested reducing service costs and increasing staff availability to improve primary healthcare utilisation. Conclusion: Most women prefer non-formal places for delivery, which has important implications for improving the state’s maternal and child health services.